The cost of firearm violent crime in British Columbia, Canada - Rajabali, Fahra; Turcotte, Kate; Zheng, Alex; Pauls, Nick; Nguyen, Tony; Kalman, Evelyn; Covic, Vedrana; Pike, Ian (Frontiers in Public Health, 2023)
This study aimed to quantify the total cost of violent firearm-related offenses in British Columbia in 2016 Canadian dollars over a five-year period, 2012 to 2016. The purposes of this study were to estimate the direct costs to the health care system and indirect costs to society for violent firearm injuries and deaths; and to estimate criminal justice system costs pertaining to firearm incidents. Human and economic costs to the health care system and productivity losses were calculated using health administrative datasets such as B.C. Vital Statistics and Discharge Abstract Database. Criminal justice system costs pertaining to firearm incidents were estimated by applying weighted average costs to aggregate expenditures using methodology consistent with that used by Statistics Canada. There was a total of 108 deaths and 245 hospitalizations resulting from violent firearm injuries. The total estimated cost of all violent firearm crime averaged 294,378,985 per year; human costs averaged 188,416,841 per year, where health care costs averaged 3,910,317 per year, productivity losses from workforce and household averaged 17,299,054 and 4,559,470 per year, respectively, and loss of life averaged 162,648,000; and 105,021,145 in criminal justice system costs, and 941,000 in programming costs. This study clearly demonstrates the significant cost of violent firearm injury in British Columbia and the impacts on the health care system, criminal justice system, and to society at large, particularly within the criminal justice system where the costs were significantly higher than health care.